Phase formation and phase stability for the homogenous and heterogeneous amorphous metals versus the crystalline phase - Yidi Shen; Konrad Samwer; William L. Johnson; William A. Goddard; Qi An (Proceedings of the National Academy of Sciences, 2025)
From molecular dynamics (MD) simulations of melt-quenching and thermal aging procedures in pure Ag, Cu, Ag–Cu binary alloys, and Cu–Zr binary alloys, we have identified two distinct amorphous phases for a metastable undercooled liquid: the homogeneous L-phase with low shear rigidity and the heterogenous G-phase with much higher shear rigidity and a heterogeneity length scale Λ. Here, we examine two-phase equilibration studies showing that the G-phase melts to form the L-phase above ~1,000 K, which then transforms to form the crystal (X) phase; however, below the melting point of the G-Phase (~990 K), the X- and G-phases do not transform into each other. We suggest the presence of a G-phase is likely responsible for embrittlement often observed in metallic glasses. We also consider how mechanical milling or irradiation-induced defect accumulation in the crystalline metallic alloy triggers a crystal-to-glass transition. We use the Cu 2 Zr system as a model to investigate random interchange of Zr and Cu atoms at room temperature leading to a transition from a crystalline Laves-phase to an L-glass through formation and growth of amorphous regions and destabilization of the crystal. During relaxation of the nonequilibrium structures by annealing, the configurations either reverted to the crystalline phase or evolve to a heterogeneous G-phase equivalent to the G-phase formed during thermal quenching and aging of the melt. Athermal defect accumulation in the G-phase at low temperature led to a transition back to the L-phase. Our findings show how athermal disordering drives transitions among the X-, L-, and G-phases.